Towards an Integrated Design of Direct-Drive Wind Turbine Electrical Generator Supporting Structures - Lucas Touw; Pablo Jaen Sola; Erkan Oterkus (Wind, 2023)
Rotor and stator support structures of significant size and mass are required to withstand the considerable loads that direct-drive wind turbine electrical generators face to maintain an air-gap clearance that is open and stable. With the increase of scale, reducing the weight and environmental impact of these support structures is believed to be one of the key components to unlocking the true potential of direct-drive generators. An investigation on the electrical generator rotor structure of the IEA 15 MW offshore reference wind turbine was conducted. An integrated approach that considered the environmental impact, including the manufacturing energy usage and CO2 footprint, as well as the financial repercussions of structural parameter modifications as they are optimised was followed, making use of distinct commercial pieces of software. The rotor structure was parametrically optimised, and its operating loading conditions were evaluated at various size scales. The study determined that the effect of thermal loading is significant, which forces the designer to augment the mass to comply with the imposed structural requirements. The ensuing life-cycle assessment showed an increase in the environmental impact due to the consideration of this particular load, whose effect in structural deflection and stress has been typically underestimated.